2011
DOI: 10.1029/2011wr010429
|View full text |Cite
|
Sign up to set email alerts
|

Capturing aquifer heterogeneity: Comparison of approaches through controlled sandbox experiments

Abstract: [1] Groundwater modeling has become a vital component to water supply and contaminant transport investigations. These models require representative hydraulic conductivity (K) and specific storage (S s ) estimates, or a set of estimates representing subsurface heterogeneity. Currently, there are a number of approaches for characterizing and modeling K and S s heterogeneity in varying degrees of detail, but there is a lack of consensus for an approach that results in the most robust groundwater models with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 75 publications
1
67
1
Order By: Relevance
“…This material was packed to match a heterogeneity pattern drawn on the glass side of the sandbox. The sand was slowly added to the sandbox through a tube to create thin layers (approximately 0.5-1 cm thick) and packed between each addition to achieve uniform compaction (e.g., Illman et al, 2007Illman et al, , 2010Berg and Illman, 2011).…”
Section: Packing Of Sandbox and Types Of Sands Usedmentioning
confidence: 99%
“…This material was packed to match a heterogeneity pattern drawn on the glass side of the sandbox. The sand was slowly added to the sandbox through a tube to create thin layers (approximately 0.5-1 cm thick) and packed between each addition to achieve uniform compaction (e.g., Illman et al, 2007Illman et al, , 2010Berg and Illman, 2011).…”
Section: Packing Of Sandbox and Types Of Sands Usedmentioning
confidence: 99%
“…They include numerical studies [e.g., Gottlieb and Dietrich, 1995;Yeh and Liu, 2000;Bohling et al, 2002;Yeh, 2005, 2006;Fienen et al, 2008;Ni and Yeh, 2008;Castagna and Bellin, 2009;Xiang et al, 2009;Liu and Kitanidis, 2011], followed by laboratory sandbox studies [e.g., Liu et al, 2002;Brauchler et al, 2003;Illman et al, 2007;Liu et al, 2007;Illman et al, 2008;Yin and Illman, 2009;Illman et al, 2010;Berg and Illman, 2011a;Illman et al, 2012] and then experimental field studies [e.g. Bohling et al, 2007;Li et al, 2007;Straface et al, 2007;Cardiff et al, 2009;Illman et al, 2009;Berg and Illman, 2011b;Brauchler et al, 2011;Huang et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, several numerical and field studies have demonstrated how steadystate hydraulic tests can be used to image hydraulic conductivity or transmissivity (e.g., [12,21,40,59]). Transient pumping tests can also be used to estimate both of the specific storage and hydraulic conductivity fields (e.g., [3,27,64]). Hydraulic conductivity tomography can also be combined with the temporal moments method to reconstruct the hydraulic parameters heterogeneities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The SLE approach has proven to be an efficient tool in hydraulic tomography. Its success has been demonstrated in saturated flow synthetic tests [59,64]; [60,58]; [51], in variably-saturated flow synthetic tests [42], in pneumatic tomography [44], in sandbox experiments [3,32,40,41], and in field experiments [4,6,30,31,49].…”
Section: Introductionmentioning
confidence: 99%